Lectotipificación de algunas bignoniaceas argentinas nativas - Arbo, María Mercedes (Instituto de Botánica del Nordeste, 2017)
Durante la revisión nomenclatural de las Bignoniaceae argentinas nativas, noté que algunos nombres no habían sido tipificados, y que algunas tipificaciones previas precisaban ajustes. La investigación nomenclatural llevó a la designación de lectotipos para Amphilophium vauthieri, Anemopaegma clematideum, Argylia uspallatensis, Arrabidaea rhodantha, A. rhodantha var. elliptica, A. rhodantha var. induta, Bignonia balbisiana, B. balbisiana var. glabra, B. difficilis, B. pterocarpa, B. samydoides, B. selloi, B. vitalba, B. vitalba var. extratropica, Dolichandra cynanchoides, Eccremocarpus scaber var. sepium y Petastoma truncatum var. parviflorum.

While working on a nomenclatural revision of Bignoniaceae native to Argentina, I noticed that some names still needed typification and that some of the earlier typifications needed adjustments. This research led to the designation of lectotypes for the following names: Amphilophium vauthieri, Anemopaegma clematideum, Argylia uspallatensis, Arrabidaea rhodantha, A. rhodantha var. elliptica, A. rhodantha var. induta, Bignonia balbisiana, B. balbisiana var. glabra, B. difficilis, B. pterocarpa, B. samydoides, B. selloi, B. vitalba, B. vitalba var. extratropica, Dolichandra cynanchoides, Eccremocarpus scaber var. sepium, and Petastoma truncatum var. parviflorum.
Lectotypification of some bignoniaceae native to Argentina
Keywords: Argentina; Bignoniaceae; Flora nativa; Lectotipificación; Nomenclatura; Argentina; Bignoniaceae; Lectotypification; Native flora; Nomenclature